2019
DOI: 10.1080/14786419.2019.1647426
|View full text |Cite
|
Sign up to set email alerts
|

Two new 8-isopentenyl isoflavane derivatives from Astragalus dolichochaete diels

Abstract: Astragali Radix (Huangqi) is one of the well-known traditional Chinese medicines and has been used in China for more than two thousand years. As a close species, Astragalus dolichochaete Diels was found to possess cytotoxicity during our preliminary study of Astragalus plants from Yunnan Province, China. To better understand the chemical foundation of the cytotoxicity, the major constituents of A. dolichochaete were studied. As a result, two new 8-isopentenyl isoflavane derivatives, dolichochaeteins A and B (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Isoflavane, a subclass of isoflavonoids, has been shown to exhibit anti-proliferative effects against various types of cancer cell lines and cause apoptosis via different molecular mechanisms. ( Hsu et al, 2011 ; Tsai et al, 2011 ; Jiang et al, 2016 ; Kaennakam et al, 2017 ; Wang et al, 2018 ; Peng et al, 2020 ; Castillo-Bautista et al, 2021 ; Wang et al, 2021 ). In this study, ShtIX was found to have stronger cytotoxicity against NSCLC cells than other cancer cells, as we were able to show here.…”
Section: Introductionmentioning
confidence: 99%
“…Isoflavane, a subclass of isoflavonoids, has been shown to exhibit anti-proliferative effects against various types of cancer cell lines and cause apoptosis via different molecular mechanisms. ( Hsu et al, 2011 ; Tsai et al, 2011 ; Jiang et al, 2016 ; Kaennakam et al, 2017 ; Wang et al, 2018 ; Peng et al, 2020 ; Castillo-Bautista et al, 2021 ; Wang et al, 2021 ). In this study, ShtIX was found to have stronger cytotoxicity against NSCLC cells than other cancer cells, as we were able to show here.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition of Astragalus is complex and mainly includes flavonoids, saponins, and polysaccharide compounds, as well as amino acids and trace elements ( Wang et al, 2021a ). To date, more than 200 compounds have been isolated from Astragalus species, among which isoflavones such as calycosin (CAL), calycosin-7-glucoside (CG), formononetin (FMN), and ononin (ON) have significant value because of their significant antioxidant, anticancer, anti-inflammatory, and neuroprotective pharmacological effects ( Jin et al, 2014 ; Yu et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is often used to treat cancer, frequent colds, and shortness of breath. [ 10 ] According to modern pharmacological investigations, AM and its ingredients are thought to have immunomodulatory, antioxidant, anti-inflammatory, anti-diabetic, and antiviral properties. [ 11 ] AM is also commonly used in the treatment of oral inflammatory diseases like OU and periodontitis.…”
Section: Introductionmentioning
confidence: 99%